Caracterização da prática dos terapeutas ocupacionais na atenção à dor oncológica de pacientes hospitalizados em cuidados paliativos - Souza Junior, Odair José Mendes (Universidade Federal de São Carlos, 2025)
Pain is one of the most common symptoms experienced by people with cancer in palliative care. Palliative care requires an interdisciplinary and multidisciplinary approach, considering the premises of comprehensive care. The occupational therapist is part of the care team, aiming to promote the maintenance of the occupational repertoire of these individuals with pain. The study aimed to characterize the practice of occupational therapists in the care of oncological pain of hospitalized patients in palliative care. This is descriptive research with a qualitative approach, and occupational therapists working in hospital wards, in oncological palliative care, with a minimum of 3 months of experience were eligible for participation. Participants were recruited using the snowball method and data were collected through interviews on a virtual platform, which were guided by a characterization form and interview script. The information from the characterization form was analyzed using simple descriptive statistics and the interview data were processed using Bardin's thematic analysis. Ten occupational therapists participated, with an average of approximately 5 years of experience in hospital settings and 4 years in palliative care. The interview data were grouped into 3 categories. The first category was called “Modus operandi of occupational therapists’ practice in cancer pain care” and covered content related to the operationality of the care offered. In this sense, 4 subcategories emerged: Work routine, Knowledge and use of pain assessment instruments, Resources and techniques used for cancer pain management, and Documentation in medical records. The second category, called “Considerations on the repercussions of cancer pain in occupations”, involved information on the professionals’ perception of the influences of pain in occupations. Finally, the category “Challenges faced in cancer pain management” presented the manifestations about difficulties faced in the context of this practice. It was found that there are evaluative weaknesses in the assistance described, regarding the appropriation of instruments and restriction of evaluative components considered in the assessment and reassessment of pain, which may hinder the production of indicators on the effectiveness and importance of the occupational therapist in the team. On the other hand, perspectives of action were noted in which professionals consider associations of pain with occupations, mainly regarding the interference of the symptom in activities of daily living, a factor that characterizes specificities of this professional activity.
Characterization of the practice of occupational therapists in the care of cancer pain in hospitalized patients in palliative care
Keywords: Dor oncológica; Terapia ocupacional; Cuidados paliativos; Prática profissional; Cancer pain; Occupational therapy; Palliative care; Professional practice; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL